Financial Flexibility as an Investment Efficiency Factor in Asian Companies - Victoria Cherkasova; Evgeny Kuzmin (Gadjah Mada International Journal of Business, 2018)
This study explores the impact of a company’s financial flexibility on the effectiveness of its investments.The number of companies that have financial flexibility was calculated with the application of thespare debt capacity method. The research identifies the impact of financial flexibility on investment activity and on the level of suboptimal investments. The data from 1,736 companies in theAsian region, during the 2005-2015time period, are presented. The Asian region has unique institutional, economic and commercial environments that present a great basis for this paper. The results of the research reveal that financially flexible companies spend more on their investment expenditure and conduct more effective investment policiesby reducing the level of over- and underinvestment. Financial flexibility helps companies to make effective investments during a crisis period, but the difference in the flexibility between developed and developing countries and between large and small companies was not observed.